2006
DOI: 10.1210/jc.2006-0620
|View full text |Cite
|
Sign up to set email alerts
|

Potent Inhibitory Effects of Type I Interferons on Human Adrenocortical Carcinoma Cell Growth

Abstract: IFNbeta1a is much more potent than IFNalpha2b to suppress ACC cell proliferation in vitro by induction of apoptosis and cell cycle arrest. Further studies are required to evaluate the potency of IFNbeta1a to inhibit tumor growth in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 32 publications
3
33
1
Order By: Relevance
“…Culture conditions of human NCI-H295R and SW13 ACC cells have been described previously (van Koetsveld et al 2006). Briefly, the cells were cultured without (vehicle only) or with substances for 7 days.…”
Section: Cell Lines and Culture Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Culture conditions of human NCI-H295R and SW13 ACC cells have been described previously (van Koetsveld et al 2006). Briefly, the cells were cultured without (vehicle only) or with substances for 7 days.…”
Section: Cell Lines and Culture Conditionsmentioning
confidence: 99%
“…In both cell lines, type 1 IFNs block the S-phase of the cell cycle. In H295 cells, but not in SW13 cells, IFN-b strongly induced apoptosis, partially mediated via inhibition of IGF2 expression, an important growth factor in ACC (de Fraipont et al 2005, van Koetsveld et al 2006. There are no data with respect to the effects of both mitotane and type 1 IFNs in primary cultures of ACC.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Notwithstanding IFN-␤ half-life (1 h) is shorter than that of IFN-␣ (4 -7 h), several studies showed that IFN-␤ has more potent antitumor effects than IFN-␣, via the activation of apoptosis (6,8,12,16,27,(31)(32)(33). In addition, new strategies could improve in future the pharmacokinetic and pharmacodynamic profile of IFN-␤, like the pegylated formulation (21).…”
Section: Discussionmentioning
confidence: 99%
“…The primer and probe sequences were purchased from Biosource (Nivelles, Belgium). The sequence of the primers for IGF-II and the concentrations of primers and probes used in the assay have been described previously by van Koetsveld et al (31). The other primer and probe sequences were as follows: IGF-I forward, 5Ј-TTGTGATTTCTTGAAGGTGAA-GATG-3Ј; IGF-I reverse, 5Ј-CGTGGCAGAGCTGGTGAAG-3Ј; IGF-I probe, 5Ј-FAM-TACCTGGCGCTGTGCCTGCTCA-TAMRA-3Ј; IGF-IR forward, 5Ј-CCAAAACTGAAGCCGAGAAG-3Ј; IGF-IR reverse, 5Ј-GGGTCGGTGATGTTGTAGGT-3Ј; IGF-IR probe, 5Ј-FAM-AAGCAGGAACACCACGGCCG-TAMRA-3Ј; insulin receptor forward, 5Ј-GCTCACGGAGACCTGAAGAG-3Ј; insulin receptor reverse, 5Ј-CACAAACTTCTTGGCGTTCA-3Ј; insulin receptor probe, 5Ј-FAM-CGTTCTCTGCGGCCAGAGGC-TAMRA-3Ј.…”
Section: Methodsmentioning
confidence: 99%